The practices of global ethics : historical backgrounds, current issues and future prospects /: historical backgrounds, current issues and future prospects. (2016) - Bird, Frederick B (Frederick Bruce), 1938-; Twiss, Sumner B; Pedersen, Kusumita Priscilla, 1946-; Miller, Clark A; Grelle, Bruce
No abstract available